Calcium Mitigates Arsenic Toxicity in Rice Seedlings by Reducing Arsenic Uptake and Modulating the Antioxidant Defense and Glyoxalase Systems and Stress Markers - Rahman, Anisur (Biomed Res Int, 2015)
The effect of exogenous calcium (Ca) on hydroponically grown rice seedlings was studied under arsenic (As) stress by investigating the antioxidant and glyoxalase systems. Fourteen-day-old rice (Oryza sativa L. cv. BRRI dhan29) seedlings were exposed to 0.5 and 1 mM Na(2)HAsO(4) alone and in combination with 10 mM CaCl(2) (Ca) for 5 days. Both levels of As caused growth inhibition, chlorosis, reduced leaf RWC, and increased As accumulation in the rice seedlings. Both doses of As in growth medium induced oxidative stress through overproduction of reactive oxygen species (ROS) by disrupting the antioxidant defense and glyoxalase systems. Exogenous application of Ca along with both levels of As significantly decreased As accumulation and restored plant growth and water loss. Calcium supplementation in the As-exposed rice seedlings reduced ROS production, increased ascorbate (AsA) content, and increased the activities of monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR), catalase (CAT), glutathione peroxidase (GPX), superoxide dismutase (SOD), and the glyoxalase I (Gly I) and glyoxalase II (Gly II) enzymes compared with seedlings exposed to As only. These results suggest that Ca supplementation improves rice seedlings tolerance to As-induced oxidative stress by reducing As uptake, enhancing their antioxidant defense and glyoxalase systems, and also improving growth and physiological condition.